2017
DOI: 10.1158/1078-0432.ccr-17-0017
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Variant AR-V9 Is Coexpressed with AR-V7 in Prostate Cancer Metastases and Predicts Abiraterone Resistance

Abstract: Purpose Androgen receptor (AR) variant AR-V7 is a ligand-independent transcription factor that promotes prostate cancer resistance to AR-targeted therapies. Accordingly, efforts are underway to develop strategies for monitoring and inhibiting AR-V7 in castration-resistant prostate cancer (CRPC). The purpose of this study was to understand whether other AR variants may be co-expressed with AR-V7 and promote resistance to AR-targeted therapies. Experimental Design We utilized complementary short- and long-read… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 50 publications
3
109
0
Order By: Relevance
“…A recent publication showed that another splice variant may also play an important role in the NHT resistance mechanism. Kohli et al stated that initial annotation of the splice variant AR-V9 needs to be reevaluated, as they revealed by short-and long-read sequencing that the sequences of the 3Ј-UTR of AR-V7 and AR-V9 overlap (34 ). This implies that our AR-V7 assay may partially also detect AR-V9.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A recent publication showed that another splice variant may also play an important role in the NHT resistance mechanism. Kohli et al stated that initial annotation of the splice variant AR-V9 needs to be reevaluated, as they revealed by short-and long-read sequencing that the sequences of the 3Ј-UTR of AR-V7 and AR-V9 overlap (34 ). This implies that our AR-V7 assay may partially also detect AR-V9.…”
Section: Discussionmentioning
confidence: 98%
“…This implies that our AR-V7 assay may partially also detect AR-V9. Nevertheless, the authors also found that AR-V9-expressing cells had similar therapeutic resistance toward the NHT drug enzalutamide as the AR-V7-expressing cells (34 ). The patients we enrolled in our study were selected for establishing the in situ assay, rather than an evaluation of patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several AR splice variants (AR-V1, -V7, and -V9) lacking LBD are also commonly reported ( Figure 2). Another splice variant, AR-V567es is also reported in prostate tumor [34][35][36][37]. Studies have documented that even though some AR variants lack LBD, they retain their ability to bind to DNA and promote constitutive gene transcription in the absence of androgens [38,39].…”
Section: Androgen Receptor: Structure and Mechanisms Of Actionmentioning
confidence: 99%
“…Clinical trials assessing the efficacy of cabazitaxel in patients with AR-V7-positive cases have shown promising results [65]. These variants can act independent of ligand-binding and hence confer resistance to ADT, enzalutamide, and abiraterone [36,[66][67][68][69].…”
Section: Ar Amplification/overexpression and Alternative Splicingmentioning
confidence: 99%
“…The availability of third generation long read technologies provides an unprecedented and nearly complete picture of isoform structures. However, existing long read transcript sequencing for human disease genes have used an amplicon-based approach (Treutlein et al 2014;Tseng et al 2017;Kohli 2017). While this approach has been successful in identifying complex alternative splicing in human disease genes, it is limited to the PCR primer design and will not uncover alternative start and end sites.…”
Section: Introductionmentioning
confidence: 99%